Antimicrobial photodynamic therapy in rat experimental candidiasis: evaluation of pathogenicity factors of Candida albicans - Martins, Joyce da Silva [UNESP]; Junqueira, Juliana Campos; Faria, Raquel Lourdes; Santiago, Naiara Fonseca; Rossoni, Rodnei Dennis; Dias Colombo, Carlos Eduardo; Cardoso Jorge, Antonio Olavo (Elsevier B.V., 2011)
Objective. This study evaluated the effects of photodynamic therapy on pathogenicity of Candida albicans.Study design. Fifty-six rats were submitted to development of candidiasis on the tongue dorsum by C. albicans inoculations. After 5 days, different treatments were administered: laser and photosynthesizer methylene blue (L+P+); laser only (L+P-); photosensitizer only (L-P+);and physiologic solution only (L-P-). Samples of the oral cavity were collected for a count of colony-forming units per mL. Colonies were isolated for evaluation of proteinase and phospholipase activities. The rats were killed for microscopic analysis of the tongue dorsum. The data were analyzed by analysis of variance, Kruskal-Wallis, and Bonferroni tests.Results. The number of C. albicans recovered from the oral cavity of the rats was similar between the groups (P = .106). The L+P+ group showed fewer microscopic lesions of candidiasis than the L-P- group (P = .001). The L+P+ group presented lower proteinase activity compared with the other groups, with significant difference between the groups L+P+ and L-P+ (P = .018).Conclusions. Photodynamic therapy reduced the microscopic lesions of experimental candidiasis in rats and inhibited the proteinase activity of C. albicans. (Oral Surg Oral Med Oral Pathol Oral Radiol Endod 2011;111:71-77)